2016
DOI: 10.1007/s00405-016-4141-z
|View full text |Cite
|
Sign up to set email alerts
|

CT findings of the temporal bone in CHARGE syndrome: aspects of importance in cochlear implant surgery

Abstract: To provide an overview of anomalies of the temporal bone in CHARGE syndrome relevant to cochlear implantation (CI), anatomical structures of the temporal bone and the respective genotypes were analysed. In this retrospective study, 42 CTs of the temporal bone of 42 patients with CHARGE syndrome were reviewed in consensus by two head-and-neck radiologists and two otological surgeons. Anatomical structures of the temporal bone were evaluated and correlated with genetic data. Abnormalities that might affect CI su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 30 publications
2
29
1
Order By: Relevance
“…In the literature, the radiographic findings of otologic abnormalities in CHARGE syndrome underscore this wide range of cochlear and vestibular abnormalities. In a recent series of 42 patients with CHARGE syndrome, CT scans revealed abnormalities of the cochlea, semicircular canals, middle ear, and internal auditory canal . Common findings included underdeveloped or absent semicircular canals (77%), hypoplastic cochleas (38%), stenotic cochlear apertures (37%), and abnormal course of the facial nerves (19%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the literature, the radiographic findings of otologic abnormalities in CHARGE syndrome underscore this wide range of cochlear and vestibular abnormalities. In a recent series of 42 patients with CHARGE syndrome, CT scans revealed abnormalities of the cochlea, semicircular canals, middle ear, and internal auditory canal . Common findings included underdeveloped or absent semicircular canals (77%), hypoplastic cochleas (38%), stenotic cochlear apertures (37%), and abnormal course of the facial nerves (19%).…”
Section: Discussionmentioning
confidence: 99%
“…Ear abnormalities are present in over 90% of patients and range from auricular malformations to ossicular dysplasia to inner ear anomalies, including dysplasia of the cochlea or semicircular canals. Over 80% of CHARGE patients have hearing loss as a result . Herein, we present the clinical case, radiologic findings, autopsy, and temporal bone pathology in an infant with CHARGE syndrome and bilateral cochleovestibular hypoplasia.…”
Section: Introductionmentioning
confidence: 95%
“…Round window absence is a rare abnormality that may be seen in conjunction with various syndromes, including incomplete partition anomalies, mandibulofacial dysostosis, and Coloboma of the eye, Heart defects, Atresia of the choanae, Retardation of growth and/or development, Genital and/or urinary abnormalities, and Ear abnormalities and deafness (CHARGE) syndrome, in addition to cases of aural atresia (Fig 3). [9][10][11] In very rare cases, it may also occur without an associated syndrome (Fig 4). 12,13 Some authors have posited that such nonsyndromic cases may represent an inherited autosomal dominant genetic disorder with variable penetrance.…”
Section: Developmental Anomaliesmentioning
confidence: 99%
“…Middle ear pathology, such as dysplastic ossicles or an absent/stenotic oval or round window, is seen on mastoid CT in over 70% of patients (Vesseur, Verbist, et al, 2016b). In some of these children a bone‐anchored hearing aid (BAHA, sometimes known as BCD—bone conductive device) may be a good hearing solution.…”
Section: Value Of Cranial Imaging In Treatment and Managementmentioning
confidence: 99%
“…One lesser‐known feature, however, is the otosclerosis‐like fusion of the stapes footplate to the cochlear oval window as described by Ogier et al (2014) in Looper mice. A recent study of CT images of the os petrosum of individuals with CHARGE syndrome showed that, in addition to the (known) abnormalities of the oval window, the stapes was dysplastic or not identifiable in half of the ears with a stenotic oval window (Vesseur, Verbist, et al, 2016b). …”
Section: Research and Cranial Imagingmentioning
confidence: 99%